Dual band printed monopole antenna design for medical implantable communication system (MICS) band - Subramaniam, Murugan (2009)
The aim of this project is to design the dual band monopole antenna to be operated in the Medical Implant Communication Service (MICS) band which is from 402MHz to 405MHz and Forced Resonance Ultra-Short Pulse Laser (FRUSPL) 50MHz ~ 1GHz. But seems there are no any recommendation for the range, frequency chosen for Forced Resonance Ultra-Short Pulse Laser (FRUSPL) band is from 150~153MHz.The whole idea of this project is to learn design method for antenna that can be resonated more than one frequency. In this thesis a single antenna operating at two different frequencies is designed. Therefore, optimization needs to carry out on few parameters to achieve best impedance matching. In other word, best impedance matching can be relate with return loss or well known as |S11| below - 10dB. This interpreted that majority of the signal transmitted reach at receiving area. In additional, the challenge in dealing with low frequency is the size of the antenna. The antenna size is inversely proportional to the operating frequency. The technique of size reduction for lower frequency antenna had learnt. In this project meandered style with branching for size reduction been introduced. Basically in this project, more focus given to monopole antenna besides other antennas. The basic characteristic of the monopole antenna is always referring to the ground as starting point. The height of antenna is from the ground. In reality, before design hardware it’s important to deal with software simulation. This is very important to avoid time waste and success in first time hardware designing. In this project, Computer Simulation System (CST) had been introduced.